Evaluation of Erythrocytes, Platelets, and Serum Iron Profile in Dogs with Chronic Enteropathy - Veronica Marchetti; George Lubas; Andrea Lombardo; Michele Corazza; Grazia Guidi; Giovanni Cardini (Veterinary Medicine International)
The aim of this study is to evaluate iron status, erythrocyte, and platelet modifications in dogs with chronic enteropathy (CE). Dogs were grouped as food-responsive diarrhea (FRD, 𝑛=11), antibiotic-responsive diarrhea (ARD, 𝑛=5), and steroid-responsive diarrhea (SRD, 𝑛=6) relating to therapeutic-response. Clinical and haematological findings, evidence of gastrointestinal blood loss, and iron metabolism were evaluated before and after treatment. A mild normocytic or microcytic anemia and thrombocytosis were identified, respectively in 18.0% and 31.8% of CE dogs. No significant differences between pre- and posttreatment of hematocrit, haemoglobin, and mean corpuscular volume, platelet count and mean platelet volume were found. Statistical analysis pointed out significant differences between pre- and posttreatment in serum iron (𝑃<.03) and unsaturated iron binding capacity (UIBC) (𝑃<.01). No significant correlations were found between these parameters and canine Inflammatory Bowel Disease activity index and pattern of CE as well.